Film blowing of linear and long-chain branched poly(ethylene terephthalate) - Härth, Michael; Dörnhöfer, Andrea (Polymers, 2020)
Film blowing of Poly(ethylene terephthalate) (PET) is challenging due its inherently low melt viscosity and poor melt strength. In this study, it is shown how the rheological properties of a commercial PET can be altered by reactive extrusion using either pyromellitic dianhydride (PMDA) or a multifunctional epoxy (Joncryl® ADR 4368) as chain extender, in order to improve the processing behavior during film blowing. The modified materials were characterized by shear and elongation rheometry and relevant processing characteristics, like melt pressure, bubble stability, and film thickness uniformity, were used to assess the influence of the type of modifier on processing and product performance. It is shown that PMDA is useful to increase the melt strength which leads to an improved bubble stability, while epoxy modified PET shows a reduced drawability that can cause problems at high take-up ratios. On the other hand, the epoxy modifier indicates a pronounced strain hardening during elongational deformation, and therefore leads to a better film thickness uniformity compared to the neat PET and the PET modified with PMDA. The differences with respect to processing performance are discussed and ascribed to the molecular structure of the materials.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Chain extender; Extensional viscosity; Film blowing; Film uniformity; Long-chain branches; Poly(ethylene terephthalate); Rheology